Analisis Etika Profesi dan Emotional Intelligence Terhadap Pengambilan Keputusan Oleh Auditor - Anjelika Denya Putri; Anisa Nainggolan; Ratih Kusumastuti (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2024)
This study seeks to explore: (1) The impact of professional ethics on auditors' decision-making, and (2) The effect of emotional intelligence on auditors' decision-making. The research employs probability sampling through a simple random sampling method, with a sample size of 40 respondents. Data collection involved the distribution of 40 questionnaires to internal auditors at BPKP Jambi Province. Path analysis using the trimming model is utilized as the analytical technique. The findings indicate that: (1) Decision-making by auditors significantly influences professional ethics, (2) Emotional intelligence significantly influences auditors' decision-making, and (3) Professional ethics and emotional intelligence collectively and significantly influence auditor decision-making.